Pro- and anti-inflammatory responses of peripheral blood mononuclear cells induced by Staphylococcus aureus and Pseudomonas aeruginosa phages - Van Belleghem, Jonas D.; Clement, Frédéric; Merabishvili, Maya; Lavigne, Rob; Vaneechoutte, Mario (Scientific reports, 2017)
The ability of bacteriophages to kill bacteria is well known, as is their potential use as alternatives to antibiotics. As such, bacteriophages reach high doses locally through infection of their bacterial host in the human body. In this study we assessed the gene expression profile of peripheral blood monocytes from six donors for twelve immunity-related genes ( i . e . CD14 , CXCL1 , CXCL5 , IL1A , IL1B , IL1RN , IL6 , IL10 , LYZ , SOCS3 , TGFBI and TNFA ) induced by Staphylococcus aureus phage ISP and four Pseudomonas aeruginosa phages ( i . e . PNM, LUZ19, 14-1 and GE-vB_Pae-Kakheti25). The phages were able to induce clear and reproducible immune responses. Moreover, the overall immune response was very comparable for all five phages: down-regulation of LYZ and TGFBI , and up-regulation of CXCL1 , CXCL5 , IL1A , IL1B , IL1RN , IL6 , SOCS3 and TNFA . The observed immune response was shown to be endotoxin-independent and predominantly anti-inflammatory. Addition of endotoxins to the highly purified phages did not cause an immune response comparable to the one induced by the (endotoxin containing) phage lysate. In addition, the use of an intermediate level of endotoxins tipped the immune response to a more anti-inflammatory response, i . e . up-regulation of IL1RN and a strongly reduced expression of CXCL1 and CXCL5.